THE FAULT IN OUR STARS - Green, John, 1977-, (Penguin Books, 2013)
Sixteen-year-old Hazel, a stage IV thyroid cancer patient, has accepted her terminal diagnosis until a chance meeting with a boy at cancer support group forces her to reexamine her perspective on love, loss, and life.